The Influence Of Job Conflict And Job Stress Through Job Satisfaction Of Employee Performance At Mulia Store Payakumbuh - Putri, Cindy Virgia (Riset Sinergi Indonesia, 2023)
Mulia Store Payakumbuh is a shopping center for fashion products. Companies must be able to create a conducive work environment in order to achieve these goals managing work conflict and work stress among employees, but this needs to be done supported by paying attention to job satisfaction. If this can be implemented will have a good impact on the company and hopefully the employees performance can improve. Therefore, this research aims to determine its effect work conflict and work stress through job satisfaction in employees show. The sample size in this study was 30 Smart user respondents The PLS analysis tool and data collection technique in this research is by distributing questionnaires using a Likert scale. Findings in results This research shows that the most dominant influence on job satisfaction is work conflict that has a negative and significant influence. This shows that The higher the work conflict felt by employees, the more it can influence their attitudeson work which can ultimately result in reduced job satisfaction. Meanwhile, the most dominant influence is on employees performance is job satisfaction which has a positive and significant influence, with employee enjoyment and satisfaction regarding their role and work, This will have a positive impact on improving employee performance. The most dominant is indirect The effect is that work conflict has a negative and significant effect on employee performance through worksatisfaction. This shows that work conflict has an impact on job satisfaction and employee performance.